Are the first year medicos empathetic? - Anly Antony; Anu Francis; Aaron David Kotturan; V Bhagyam (Wolters Kluwer Medknow Publications, 2018)
Background: Empathy is an essentiality among the medical fraternity. Literature indicates better competency, patient compliance and clinical outcomes in relation to higher levels of empathy. Gender differences in empathy level are universal and various factors influence it. So it's quintessential to understand empathy and its correlates among medicos in India. Aims: To evaluate changes in empathy levels of the M.B.B.S students of a renowned medical college in India, during their course in the first year. Materials and methods: A prospective study was carried out among hundred 1st year medical students [M=34,F= 66] enrolled at a medical college in Kerala during the academic year 2014-2015. Participants completed the Jefferson Scale of Empathy [Student Version]. Results: The mean empathy at the entry & exit points of the study stood at 112 ± 11.39 & 112.07 ± 13.98 respectively. Comparing the male & female population, the females had higher empathy levels. When comparing the empathy levels at the entry & exit points of the male population, significant decline [p value = 0.001] was seen. The female population showed a significant increase [p value = 0.001] in their empathy levels over the same period. Conclusion: There were significant changes in empathy levels of the male & female population, though discernable changes in the whole population were not evident. This study necessitates further follow up of the present students, to analyze the changes occurring over the entire period of medical school.